If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5x-1=4x-37
We move all terms to the left:
-5x-1-(4x-37)=0
We get rid of parentheses
-5x-4x+37-1=0
We add all the numbers together, and all the variables
-9x+36=0
We move all terms containing x to the left, all other terms to the right
-9x=-36
x=-36/-9
x=+4
| (8r+9)-5=68 | | 6g+5=4g-2-3g | | 80+x0.50=100 | | 5v^-30v=0 | | ½x+9=-11 | | -5x+1=7x-13 | | 100=-5(3v-4) | | -4(2x+10)=-16 | | -3-2x+6=-5x | | 7m-8=m+28 | | 11d–13=12d+1 | | 36/45=n/5 | | 3j+12=39 | | –4(y+5)–3y+15=30 | | 25=4x-7x+4 | | 11d–13=12d+1 | | 2x^2+24-6=0 | | (4/3(x+2))-2/3x=1/(x+2) | | 9x+7/4=7x-5/5+7 | | 3-7y=6 | | 13/130=x/10 | | 4(k-15)-(-17)=17 | | 7(5n-1)=-217 | | Y=3(y+2) | | -7=-1/3k+8 | | 27=6x-2x-5 | | 4(k-15)-17=17 | | 8(f+3)=88 | | –2(6a–7)=–2 | | 4/3(x+2)-2/3x=1/(x+2) | | -2(8x-3)+3x=2(x+8) | | 9=4(x+9)-7=25 |